ANALYSIS OF METHODS FOR INCREASING THE EFFICIENCY OF GAS TURBINE UNIT OPERATION - Volyanska, Larysa; Pikul, Maryna; Otroshchenko , Volodymyr (Science-based technologies, 2021)
A promising direction in the development of the energy sector is the use of energy–saving technologies based on gas turbine units, which can significantly increase the efficiency of fossil fuel use. One of the promising ways to improve the fuel efficiency of gas turbine plants is the use of complex thermodynamic cycles. The article presents a study of increasing the efficiency of gas turbine plants by improving their thermal and technological schemes. The schemes with intermediate cooling in the process of air compression and with heat recovery of exhaust gases are considered. The article discusses the problem of optimization and selection of rational parameters of the working process of a gas turbine plant. Integrated optimization of the parameters of the thermodynamic cycle of a gas turbine unit, such as the gas temperature in front of the turbine, compressor pressure ratio, as well as the parameters that determine the working process of additional units of the plant, plays an important role in increasing its efficiency. The AI–336–1 / 2–10 gas turbine drive, designed to drive gas–pumping units and other industrial plants with a capacity of 10 MW, was chosen as the object of the study.Selecting workflow parameters that provide maximum efficiency is a major challenge in the design of complex cycle motors.The results of a numerical study of the influence of the main parameters of the operating process of the plant on the efficiency are presented, the influence of pressure ratio and the maximum cycle temperature on the cycle parameters is analyzed. The comparison of the values ​​of the optimal pressure ratio in terms of effective efficiency with the optimal pressure ratio in terms of specific effective work for cycles of a simple scheme and a complex one.It is shown that due to multistage compression with intercooling and exhaust gas regeneration; it is possible to achieve high values ​​of effective efficiency, which for a gas turbine plant of a simple scheme can be obtained only at high cycle parameters